2018
DOI: 10.3389/fphys.2018.00673
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Model Approach for Analyzing Continuous Glucose Monitoring in Type 2 Diabetes

Abstract: Continuous glucose monitoring (CGM), a technique that records blood glucose at a regular intervals. While CGM is more commonly used in type 1 diabetes, it is increasingly becoming attractive for treating type 2 diabetic patients. The time series obtained from a CGM provides a rich picture of the glycemic state of the subjects and may help have tighter control on blood sugar by revealing patterns in their physiological responses to food. However, despite its importance, the biophysical understanding of CGM is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…This paper, for the first time, proposed a glucose-based model for the successful extraction of useful physiological information on glucose metabolism in subjects with NGT, thereby overcoming the weaknesses of existing GOM approaches. [8][9][10][11][12][13] The model's independence from insulin measurements and exclusive use of easily accessible data enable further developments and its potential application in research and clinical practice to a large number of subjects. In particular, the proposed model could allow a more sophisticated physiological interpretation of CGM profiles collected under ambulatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This paper, for the first time, proposed a glucose-based model for the successful extraction of useful physiological information on glucose metabolism in subjects with NGT, thereby overcoming the weaknesses of existing GOM approaches. [8][9][10][11][12][13] The model's independence from insulin measurements and exclusive use of easily accessible data enable further developments and its potential application in research and clinical practice to a large number of subjects. In particular, the proposed model could allow a more sophisticated physiological interpretation of CGM profiles collected under ambulatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Goel et al . [91] suggested that while the linear approach used in Eq 16 is appropriate for liquid meals, it may also be used for mixed meals, albeit with a different (slower) dynamics compared to liquid meals. This issue is worth addressing here because, in general, a poor description of the rate of glucose appearance may confound the effects of other glucose transport, secretion or production mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Here A 1,3 = −1 means remote insulin decreases glucose level. This matrix was inspired and extracted from the physiological models of Goel et al (2018) and Bergman (2005). Figure 4 illustrates this matrix by representing it as the corresponding GDPM with arbitrary weights.…”
Section: Appendix a Details On Gdpmmentioning
confidence: 99%